Pathophysiological basis for utility of zoledronic acid in patients with prostate cancer - Wcisło, Gabriel (Contemporary Oncology/Współczesna Onkologia, 2008)
Prostate cancer still appears to be a very important malignant disease in Western societies. It can be said that prostate cancer morbidity rises with age in old men. The natural history of prostate cancer is rather simple. The majority of patients who are diagnosed with localized prostate cancer are treated with curative intent with either radiation or surgery. Patients in whom treatment with curative intent is unsuccessful and those who present with metastasis are candidates for androgen suppression. Skeletal-related events are defined by the existence of changes in antineoplastic therapy to treat bone pain, pathological bone fractures, radiation therapy to bone, spinal cord compression, and surgery to bone. Bone pathology correlates with cancer course and has been shown to influence survival. Pathobiology provides new insights into mechanisms responsible for bone metastases related to prostate cancer. Several studies have evaluated risk factors for bone loss and fractures in prostate cancer patients receiving androgen-deprivation therapy. The three risk factors that have been reliably identified in patients with locally advanced disease are older age, low body mass index and a long duration of androgen-deprivation therapy. In metastatic prostate cancer, the sole reliable risk factor is elevated levels of deoxypyridinoline. Zoledronic acid has a crucial impact on combined therapy with hormones, then with chemotherapy, and additionally can be used in the prevention of osteoporosis/osteopenia related to cancer treatment.